FACTORS INFLUENCING THE EFFECTIVE CAPTURE OF INDIRECT COSTS IN ACCIDENT REPORTS BY EMERGING CONSTRUCTION CONTRACTORS IN SOUTH AFRICA - Ayodeji .O. Aiyetan; Chikezirim Okorafor (Journal of Construction Project Management and Innovation)
There has been limited research into the indirect cost of accidents in the South African construction industry, despite its consequences on productivity and performance measurement and management. Extant studies have attempted to explore the impact of direct and indirect costs from a macro-economic (industry-wide) perspective.  Whilst a few have focused on the micro-economic impacts, with specific emphasis on the organizational level, most of these studies have concentrated on the construction client perspective without recourse to the experiences for construction contractors. This is the gap which this study seeks to fulfil within the South Africa. To achieve this objective, a document analysis of selected construction accident reports was conducted using a pre-set theme identified from the literature in extracting information from the emerging contractors’ accident reports. It was revealed that none of the reports were compliant as per the pre-set theme used. The reasons behind the non-compliance were sought for, through another round of data collection deploying questionnaire surveys. A population of contractors within CIDB grades 5-7 were sampled and surveyed. Survey results revealed that difficulties in extracting the information top the list with MIS value of 4.67, followed by organisational will with MIS value of 4.61. Also, areas for improvement in capturing the accident report were highlighted such as; making it as a policy for any accident report to capture indirect cost with MIS of 4.82 which ranks 1st; assigning timeliness on when the data must be captured in any accidents with MIS of 4.66 which ranks 2nd. This finding has implications on the emerging contractors as it provides information on factors that negate and impact on sustainability of the emerging contractors as it relates to OHS performance and competitiveness.